THE UTOPIAN BIOGRAFIA OF INVENCAO DE ORFEU, BY JORGE DE LIMA - Cavalcanti, Luciano Dias [UNESP] (Centro Ensino Superior Juiz De Fora, 2020)
In this article, we intend analyze the presence of utopia the Eighth Canto, Biografia, the largest Canto of Invericao de Orfeu, composed of only one resort (in decassyllable sextles) that synthetically resumes both the imagery and the theme of the previous songs. The Canto represents a poetic reflection on the situation of man from the fall to the Apocalypse and his final victory. In it, onirism, childhood and the image of the island receive a structuring character in the poem. The biography is not only that of the poet, it encompasses a broad sense of poetic tradition, childhood as creation and the desire to meet a renewed utopia, representations that can be considered the core of every poem by Jorge de Lima.
Keywords: Invencao de Orfeu; Onirismo; Childhood; Utopia